Eksekusi Jaminan Fidusia Berdasarkan Undang-Undang No. 42 Tahun 1999 Tentang Jaminan Fidusia(Studi Kasus Putusan Pengadilan Negeri No. 09/Pdt./2014/PT.TK) - Arbiyanto, Reza; , Darsono, S.H., M.Hum (2017)
This study aims to determine the execution process guarantees under Act No. 42 of 1999 concerning fiduciary to a debtor fails to pay. The method used in this research is a normative method, the type of research is descriptive research. The data source consists of primary data and secondary data. Data were collected through library research and interviews, then analyzed by methods of qualitative analysts. The results showed consideration of judges in deciding matters in this case won by the defendant was based on the facts contained in the trial and based on laws pertaining to these problems, and upheld the ruling of lower courts and in the settlement of defaulting indirect manner execute a fiduciary guarantee object, but first made persuasive ways that aims to remind the debtor that the debtor must pay the installments due've already entered the maturity date.